TEACHING READING NARRATIVE TEXT BY USING WINDOW NOTES STRATEGY TO THE EIGHTH GRADE STUDENTS OF SMP MUHAMMADIYAH 4 PALEMBANG - Ariesca Ariesca; Lenny Marzulina (Edukasi, 2016)
The purpose of this study was to find out whether or not there is a significant difference on the eighth grade students’ reading comprehension who were taught by using window notes strategy and those who were not at SMP Muhammadiyah 4 Palembang. The population of this study consisted of 140 eighth grade students of SMP Muhammadiyah 4 Palembang in Academic Year of 2014/2015. There were fifty eight students taken as sample. Each class consisted of twenty nine students from class VIII A as experimental group and twenty nine students from class VIII B as control group. The sample of this study was taken by using purposive sampling method. In this study, the researcher used pretest-posttest non-equivalent group design. The instrument used in collecting the data was reading comprehension test in the form of multiple choice. The test was administrated twice, as the pretest and posttest for both experimental and control group. The result of the test were analyzed by using IBM SPSS (Statistical Package for the Social Science) Statistics 22. The result showed that “there was means significant difference from students’ posttest scores in experimental and control groups, it was found the p-output (Sig.2-tailed) was lower than 0.05 level and t-value (4.324) is higher than t-table (1.673). So, the Ho (the null hypothesis) was rejected and Ha (the alternative hypothesis) was accepted. It means that there was significant difference on students’ reading comprehension achievement taught using window notes strategy than those who were not.